Analysis of Social Media Marketing in Starbucks Indonesia - Mirna Aulia; Irmawan Rahyadi (Syntax Idea)
In today's highly competitive business environment, effective digital marketing is essential for businesses to build brand presence and attract and retain customers. In Indonesia, internet users are increasing from year to year because they can access anything and easily explore the things they want to know. This research aims to analyze the digital marketing and social media content of Starbucks Indonesia. This research approach is a qualitative approach. In this research, the case study that will be used is Multiple Case Study. This research approach is a qualitative approach. In this research, the case study that will be used is Multiple Case Study.